ANALISIS POTENSI RETRIBUSI TEMPAT REKREASI DI KABUPATEN BELU - Calixtus Efrem Bone Lau; Donny T. S. Junias; Deetje W. Manuain (JAKA - Jurnal Jurusan Akuntasi, 2020)
This study aims to measure the potential for recreational and user fees in Belu District and to conclude an appropriate tourism object development strategy to increase the acceptance of these fees. This research will be conducted in 4 (four) tourism objects managed by the Belu Regency Culture and Tourism Office, namely Pasir Putih Beach, Gurita Bay, Aufuik Beach, Susuk Pool. The data analysis technique used is Potential Analysis and SWOT Analysis. The results of the study showed that the potential for receiving recreational levies in Belu Regency was Rp. 204,778,000, with details: (1) Aufuik Beach with a potential levy of Rp. 80,482,500; (2) White Sand Beach with a potential levy of Rp. 79,462,500; (3) Gurita Bay with a potential levy of Rp. 30,812,000; and (4) Susuk Pool with a potential retribution of Rp. 14,021,000. The right strategies to increase revenue from the four tourist attractions are: (1) Strength-Threat Strategy by increasing the uniqueness of the object, using tariffs according to regulations, establishing good cooperation between related parties; (2) Strength-Opportunity Strategy by maintaining and further enhancing security, maintaining high potential and image, attracting workers from the surrounding community and conducting socialization with the local community; (3) Weakness-Threat Strategy by adding cleaning staff, clarifying and overcoming problems arising from negative issues, improving facilities and infrastructure as well as roads to objects and making affordable travel packages.